USING CIRC METHOD IN TEACHING READING COMPREHENSION ON DESCRIPTIVE TEXTS - Suparlan; Lalu Mahsar (SILABUS: Jurnal Ilmu dan Inovasi Pendidikan, 2025)
The purpose of this research is to investigate the effectiveness of the function Cooperative Integrated Reading and Composition (CIRC) Method in the proses of teaching and learning in reading comprehension on descriptive text. A pre-experimental analysis was carried out at SMAN 1 Batukliang Kabupaten Lombok Tengah Provinsi Nusa Tenggara Barat with the analysis subjects being eleven grade pupils of class B for the 2024/ 2025 academic year who were selected using the cluster random sampling method to meet the investigation target. Based on the results of the analysis, it shows that the use of the Cooperative Integrated Reading and Composition (CIRC) Method has a very significant influence on pupils' reading comprehension on descriptive texts as shown by an improvement in pupils' scores on the post-test and students' learning behavior towards reading activities. In conclusion, this research proves that teaching reading comprehension on descriptive texts using the Cooperative Integrated Reading and Composition (CIRC) technique was effective.